PENGARUH TINGGI BADAN TERHADAP KECERDASAN KOGNITIF MURID TK A AL-MUJAHIDIN CILACAP - Intarti, Wiwit Desi; Hesti Savitri, Naomi Parmila (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
The process of growth and development particularly in infancy and toddler is a process that is very important for human life. Toddlers from birth has been equipped with a level of intelligence kecerdasan.Tetapi development in toddlers is not always the same, there are growing fast and some are even very slow growing. Child's intellectual development associated with mental development in the years of his life. So great opportunities to prevent short stature made ​​as early as mungkin.dengan prevent poor nutritional risk factors in infants. The purpose of the institution is to know about the average Height and boys and girls Kindergarten A, the average achievement of learning (the development of motor and cognitive abilities) A kindergarten student, and a significant positive relationship between Height with cognitive intelligence and the influence of TB to cognitive intelligence kindergarten kindergarten students Adi Al Mujahideen Islam Cilacap. This study uses Associative research approach, which was to determine whether there is any effect of height with cognitive intelligence. The samples in this study were 80 students in kindergarten A purposive sampling taken appropriate inclusion and exclusion criteria. The research instrument used was a questionnaire about the examination and DDST II first semester grades as a result of learning achievement to measure the academic skills and Height gauges and Pearson product moment correlation. TB research results obtained by the average kindergarten boys A 103.59 cm by 93.18 cm normal TB <TB <113.98 cm, while the average Height 102.20 cm women with normal Height 93.72 cm <TB <110.68 cm. Achievement of learning (the development of motor and cognitive abilities) average kindergarten student A boys and girls Kindergarten A is sufficient; cognitive development while the average kindergarten boys category A is sufficient; and cognitive development girls average kindergarten category A is good. There was no relationship Height (in above-average and below average) with cognitive intelligence kindergarten pupil A. Influence of height on cognitive intelligence A kindergarten pupil in kindergarten Islam Al Mujahideen Cilacap is weak determinant coefficient <20% and still influenced by other factors enumerated by> 80%. Keywords: Height, Cognitive Intelligence, A kindergarten student